Method for preparing surface-functionalized flexible composite fiber membrane and application thereof
Patent Information
- Application Number
- CN202310877300.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-17
AI Technical Summary
[0005]本发明的目的是提供一种表面功能化柔性复合纤维膜的制备方法及其应用,解决了目前如何实现PVDF/HHE纳米纤维膜表面贵金属纳米颗粒尺寸的精确控制,以及在该复合材料的应用中存在的SERS信号容易受到物理活动影响的问题
[0019]本发明的有益效果是,本发明表面功能化柔性复合纤维膜的制备方法及其应用,采用的多次吸附再还原的方式在PVDF/HHE纳米纤维膜上制备出金种子。通过多种试剂配合降低生长溶液中银离子的还原电位及反应速度,使生长溶液中的Ag离子无法形核。从而Ag会以PVDF纳米纤维表面的金种子为活性位点,沉积在其表面。通过不同循环生长的次数,实现对PVDF/HHE纳米纤维膜表面Ag纳米颗粒尺寸的精确控制。
Smart Images

Figure CN116791363B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterial preparation technology, specifically relating to a method for preparing a surface-functionalized flexible composite fiber membrane and its application. Background Technology
[0002] Flexible plasma nanofiber membranes have attracted considerable interest from researchers due to their ability to manipulate, adjust, and focus light at the nanoscale (D. Chen, T. Chen, Y. Li, et al. Nano, 2021, 16(04): 2150044.). The exponential amplification of the output Raman scattering signal by the plasma substrate provides an opportunity to develop wearable spectral sensing mechanisms. Ag nanostructures have larger optical cross-sections and lower manufacturing costs, making them excellent materials for fabricating plasma substrates. Flexible polyvinylidene fluoride (PVDF) has important application value in photoelectric sensing due to its different chain conformations (X. Liu, J. Ma, X. Wu, et al. ACSnano, 2017, 11(2): 1901-1910.). Generally, the β phase of highly polar PVDF exhibits piezoelectric properties suitable for producing piezoelectric sensors (S. Cheon, H. Kang, H. Kim, et al. Advanced Functional Materials, 2018, 28(2): 1703778.). Plasmon functionalization of polyvinylidene fluoride (PVDF) fiber surfaces may be a feasible approach to achieving integrated and multifunctional sensing mechanisms. However, another noteworthy issue is that the plasmon functionalization of PVDF fiber surfaces should maintain an abundant β phase to preserve their piezoelectric properties. Precisely controlling the arrangement of LSPR "hot spots" along three-dimensional space while maintaining piezoelectric properties is extremely challenging.
[0003] Surface-enhanced Raman scattering (SERS) technology is an important tool for human health monitoring, possessing high sensitivity and low detection limits, enabling rapid detection of biomolecules. In research on SERS technology, it has been successfully applied to glucose, lactic acid, proteins, nucleic acids, and bacteria. Currently, wearable SERS sensors are rarely used, primarily due to the challenge of maintaining structural stability during continuous body activity and muscle movement during wearable SERS sensing.
[0004] The activity of localized surface plasmon resonance (LSPR) is typically preserved by the nanogap generated by plasmon sensing arrays, which are highly sensitive to changes in distance and structure at the nanoscale. Therefore, anti-interference sensing mechanisms and strategies are crucial, especially for developing integrated biochemical wearable devices. Muscle movement can disintegrate the "hot spot" structure of LSPR sensing, potentially affecting the results of wearable SERS spectroscopy detection. Multilayer plasmon nanostructures exhibit better uniformity and stability of SERS signals than monolayer distributed nanostructures (xingn D.Chen, X.Zhu, J.Huang, et al. Analytical. Chemistry, 2018, 90(15):9048-9054). Multilayer "hot spots" represent a potential design that can resist the effects of deformation during wearable SERS sensing. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing a surface-functionalized flexible composite fiber membrane and its application, which solves the current problems of how to achieve precise control of the size of noble metal nanoparticles on the surface of PVDF / HHE nanofiber membranes, and the problem that the SERS signal in the application of this composite material is easily affected by physical activities.
[0006] The technical solution adopted in this invention is:
[0007] The preparation method of surface-functionalized flexible composite fiber membrane specifically includes the following steps: S1: Prepare PVDF / HHE nanofiber membrane; S2: Modify the surface of PVDF / HHE nanofiber membrane using solution A to obtain modified PVDF / HHE nanofiber membrane; S3: Immerse the modified PVDF / HHE nanofiber membrane in 10-25mM chloroauric acid for 1-2 min, rinse with deionized water, and then place it in solution B for 1-2 min. Remove the excess liquid and immerse it in anhydrous ethanol for 10-30 s; obtain PVDF / HHE@Au composite fiber membrane by repeating the above cycle two to six times; S4: Add PVP, acetonitrile, ethanol, silver nitrate, and ascorbic acid to deionized water, place the PVDF / HHE@Au composite fiber membrane in the growth solution at room temperature and stir magnetically. After the reaction, remove the membrane and remove excess liquid; obtain PVDF / HHE@Ag composite fiber membrane by repeating the above cycle two to six times.
[0008] The invention is further characterized by:
[0009] Step 1 specifically involves mixing PVDF and HHE, using N,N-dimethylformamide and acetone as solvents to obtain a mixed solution C; wherein:
[0010] The mass percentage of PVDF in mixed solution C is 10-14%, the mass percentage of HHE in PVDF is 1-3%, and the mass percentage of acetone in N,N-dimethylformamide is 25-100%.
[0011] A uniform electrospinning solution was prepared by magnetic stirring in water at 60℃-70℃ for 6-8 hours. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. The experimental steps were carried out under ambient atmospheric conditions.
[0012] In step 2, the PVDF / HHE nanofiber membrane is cut into sheets and then soaked in anhydrous ethanol for 1-2 minutes.
[0013] In step 2, solution A is anhydrous ethanol or anhydrous methanol.
[0014] In step 3, removing excess liquid specifically involves rinsing the surface with deionized water for 10-20 seconds to remove residual solution, and then squeezing out excess water using a glass plate.
[0015] In step 3, solution B can be one of sodium borohydride, hydrazine hydrate, ascorbic acid, or ammonia.
[0016] The specific parameter control in step 4 is as follows: the mass fraction of PVP is 3-8%, the concentration of silver nitrate is 0.05-0.15M, and the concentration of ascorbic acid is 0.05-0.15M; wherein, the percentage of PVP, acetonitrile, ethanol, silver nitrate, and ascorbic acid added to deionized water is controlled to be 0-150%, 0-150%, 0-150%, 2.5-15%, and 2.5-15%, respectively.
[0017] The PVDF / HHE@Ag composite fiber membrane prepared based on this method is applied to SERS sensing, specifically as follows:
[0018] One end of the PVDF / HHE@Ag composite fiber membrane is fixed, and the other end is rotated around its own axis to obtain a twisted PVDF / HHE@Ag composite fiber membrane. Finally, the twisted PVDF / HHE@Ag composite fiber membrane is used for SERS sensing.
[0019] The beneficial effects of this invention are that the preparation method and application of the surface-functionalized flexible composite fiber membrane utilize a multiple adsorption-reduction process to prepare gold seeds on a PVDF / HHE nanofiber membrane. By using various reagents to reduce the reduction potential and reaction rate of silver ions in the growth solution, Ag ions in the growth solution cannot nucleate. Consequently, Ag uses the gold seeds on the PVDF nanofiber surface as active sites and deposits on their surface. By varying the number of growth cycles, precise control of the Ag nanoparticle size on the PVDF / HHE nanofiber membrane surface can be achieved. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention;
[0021] Figure 2 This is a SEM image of the nanofibers obtained in step 1 of Example 1 of the preparation method of PVDF / HHE@Ag composite fiber of the present invention;
[0022] Figure 3 This is a SEM image of the nanofibers obtained in step 3 of Example 1 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0023] Figure 4 This is a SEM image of the nanofibers obtained in step 4 of Example 1 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0024] Figure 5 The present invention relates to a method for preparing a surface-functionalized flexible composite fiber membrane and its application, which is shown by obtaining a SERS spectrum when using a portable Raman spectrometer to detect sweat secretions.
[0025] Figure 6 This is the XRD pattern of nanofibers obtained in step 4 of Example 2 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0026] Figure 7 This is the infrared image of the nanofibers obtained in step 4 of Example 2 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0027] Figure 8 This is a SEM image of the nanofibers obtained in step 4 of Example 3 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0028] Figure 9 This is a SEM image of the nanofibers obtained in step 4 of Example 4 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0029] Figure 10This is a SEM image of the nanofibers obtained in step 4 of Example 5 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0030] Figure 11 This is a SEM image of the nanofibers obtained in step 4 of Example 6 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0031] Figure 12 The present invention relates to a method for preparing a surface-functionalized flexible composite fiber membrane and its application in obtaining SERS spectra of respiratory secretions using a Raman spectrometer.
[0032] Figure 13 This is a SEM image of the nanofibers obtained in step 4 of Example 8 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention.
[0033] Figure 14 This is an FDTD simulation diagram of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention;
[0034] Figure 15 This invention relates to a method for preparing a surface-functionalized flexible composite fiber membrane and its application in detecting MG, obtaining SERS spectra under different strains.
[0035] Figure 16 This invention relates to a method for preparing surface-functionalized flexible composite fiber membranes and its application in detecting MG (magnetic precipitates) by obtaining SERS spectra under different cyclic stretching conditions.
[0036] Figure 17 This invention relates to a method for preparing surface-functionalized flexible composite fiber membranes and its application. The results obtained during thiuram testing showed 1378 and 559 cm⁻¹ values. -1 A graph showing the relationship between SERS signal intensity at the peak position and thiuram concentration.
[0037] Figure 18 This is the SERS spectrum obtained when detecting thiuram using the preparation method of the surface-functionalized flexible composite fiber membrane of the present invention and its application.
[0038] Figure 19 The SERS spectra of 16 thiurams were randomly collected, representing the preparation method and application of the surface-functionalized flexible composite fiber membrane of this invention.
[0039] Figure 20 The present invention relates to a method for preparing a surface-functionalized flexible composite fiber membrane and its application, as well as the SERS spectrum obtained when using a Raman spectrometer to detect sweat secretions.
[0040] Figure 21The present invention relates to a method for preparing a surface-functionalized flexible composite fiber membrane and its application, which is shown by obtaining a SERS spectrum when using a portable Raman spectrometer to detect sweat secretions.
[0041] Figure 22 This is a SEM image of the nanofibers obtained in Example 7 of the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention. Detailed Implementation
[0042] The preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0043] like Figure 1 As shown, the preparation method and application of the surface-functionalized flexible composite fiber membrane of the present invention will be described in detail below through specific embodiments.
[0044] Example 1;
[0045] This invention provides a method for preparing surface-functionalized flexible composite fiber membranes and their applications, specifically including the following steps:
[0046] Step 1: Preparation of PVDF / HHE nanofiber membranes (e.g.) Figure 2 (as shown);
[0047] N,N-dimethylformamide (DMF) and acetone were mixed in a 1:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the final mass fraction of PVDF controlled at 12% and HHE at 2% of PVDF. The mixture was magnetically stirred in water at 60°C. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0048] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0049] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 20mM chloroauric acid for 1 minute. After removal, rinse the surface with deionized water for 10 seconds, then react it in 20mM sodium borohydride for 1 minute. After removal, rinse the surface with deionized water for 10 seconds to remove any remaining solution, and squeeze out excess water using a glass plate. Then immerse it in anhydrous ethanol for 10 seconds. This completes one cycle. Six cycles are performed to obtain a nanofiber membrane with gold seeds (e.g., ...). Figure 3 (As shown).
[0050] Step 4: Add 2 ml of PVP (5%), 2 ml of acetonitrile, 2 ml of ethanol, 150 μl of silver nitrate (0.1 M), and 100 μl of ascorbic acid (0.1 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 10 °C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After two cycles, the PVDF / HHE@Ag nanofiber membrane (e.g., ...) is obtained. Figure 4 (As shown). The PVDF / HHE@Ag nanofiber membrane was washed with deionized water and dried at room temperature.
[0051] By fixing one end of a PVDF / HHE@Ag nanofiber membrane and rotating the other end around its own axis, a twisted PVDF / HHE@Ag nanofiber membrane can be obtained. The twisted PVDF / HHE@Ag nanofiber membrane exhibits an increase in intersection points in three dimensions. FDTD simulations show that additional "hot spots" are generated at these intersection points. Figure 14 The density of the "points" increases, thus improving the sensitivity of SERS. Finally, SERS sensing of the MG solution was performed using a PVDF / HHE@Ag nanofiber membrane. After stretching, the SERS signal intensity of the untwisted PVDF / HHE@Ag nanofiber membrane continuously decreased; while the SERS signal intensity of the twisted PVDF / HHE@Ag nanofiber membrane decreased slightly, but still remained above 90% of the unstretched SERS signal intensity. Figure 15 It was observed that the latter, with strains of 0-30%, maintained a substantially unchanged SERS signal intensity even after 1000 cycles of stretch-relaxation. Figure 16 Therefore, it can be seen that the SERS signal stability of PVDF / HHE@Ag nanofiber membrane was improved after twisting.
[0052] Example 2;
[0053] Step 1: Prepare PVDF / HHE nanofiber membrane;
[0054] N,N-dimethylformamide (DMF) and acetone were mixed in a 1:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the final mass fraction of PVDF controlled at 12% and HHE at 3% of PVDF. The mixture was magnetically stirred in water at 60°C. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0055] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0056] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 20mM chloroauric acid for 1 minute. After removal, rinse the surface with deionized water for 10 seconds, then react it in 20mM sodium borohydride for 1 minute. After removal, rinse the surface with deionized water for 10 seconds to remove any remaining solution, and squeeze out excess water using a glass plate. Then, immerse it in anhydrous ethanol for 10 seconds. This completes one cycle. Six cycles are required to obtain a nanofiber membrane with gold seeds.
[0057] Step 4: Add 2 ml of PVP (5%), 2 ml of acetonitrile, 2 ml of ethanol, 150 μl of silver nitrate (0.1 M), and 100 μl of ascorbic acid (0.1 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 10 °C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After four cycles, the PVDF / HHE@Ag nanofiber membrane (e.g., ...) is obtained. Figure 5 (As shown). The PVDF / HHE@Ag nanofiber membrane was washed with deionized water and dried at room temperature. XRD analysis is shown below. Figure 6 As shown, the 2θ of the four main diffraction peaks appears at 38.3°, 44.6°, 64.7°, and 77.5°, corresponding to the (111), (200), (220), and (311) crystal planes of Ag face-centered cubic (fcc), respectively. Infrared analysis is as follows... Figure 7 As shown, calculations based on Lambert-Beer's law show that the β phase of the PVDF / HHE@Ag nanofiber membrane is 76.4%, which still allows for piezoelectric sensing.
[0058] By fixing one end of a PVDF / HHE@Ag nanofiber membrane and rotating the other end around its own axis, a twisted PVDF / HHE@Ag nanofiber membrane can be obtained. Finally, the PVDF / HHE@Ag nanofiber membrane is used for SERS sensing of a thiuram solution. Figure 17 As shown, the detection limit (LOD) of thiuram is 0.1 nM, and the SERS signal intensity decreases with decreasing concentration. Figure 18 Shown at 1378 and 559cm -1 A scatter plot of the SERS signal intensity at the peak position versus the thiuram concentration was generated. Linear fitting revealed a good linear relationship between the SERS signal intensity and thiuram concentration in the range of 0.1 nM–10 μM. To demonstrate the stability of the SERS signal of the PVDF / HHE@Ag nanofiber membrane, 16 SERS spectra of thiuram were randomly collected. Figure 19). Calculations show that at 1378cm -1 The relative standard deviation (RSD) at the location is approximately 8.2%, indicating that the SERS signal is relatively stable.
[0059] Example 3;
[0060] Step 1: Prepare PVDF / HHE nanofiber membrane;
[0061] N,N-dimethylformamide (DMF) and acetone were mixed in a 3:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the final mass fraction of PVDF controlled at 14% and HHE at 3% of PVDF. The mixture was magnetically stirred in water at 60°C. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0062] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0063] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 20mM chloroauric acid for 1 minute. After removal, rinse the surface with deionized water for 10 seconds, then react it in 20mM sodium borohydride for 1 minute. After removal, rinse the surface with deionized water for 10 seconds to remove any remaining solution, and squeeze out excess water using a glass plate. Then, immerse it in anhydrous ethanol for 10 seconds. This completes one cycle. Six cycles are required to obtain a nanofiber membrane with gold seeds.
[0064] Step 4: Add 2 ml of PVP (5%), 2 ml of acetonitrile, 2 ml of ethanol, 150 μl of silver nitrate (0.1 M), and 100 μl of ascorbic acid (0.1 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 10 °C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After six cycles, the PVDF / HHE@Ag nanofiber membrane (e.g., ...) is obtained. Figure 8 (As shown). The PVDF / HHE@Ag nanofiber membrane was washed with deionized water and dried at room temperature.
[0065] Example 4;
[0066] Step 1: Prepare PVDF / HHE nanofiber membrane;
[0067] N,N-dimethylformamide (DMF) and acetone were mixed in a 4:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the final mass fraction of PVDF controlled at 11% and HHE at 3% of PVDF. The mixture was magnetically stirred in water at 60°C. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0068] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0069] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 20mM chloroauric acid for 1 minute. After removal, rinse the surface with deionized water for 10 seconds, then react it in 20mM sodium borohydride for 1 minute. After removal, rinse the surface with deionized water for 10 seconds to remove any remaining solution, and squeeze out excess water using a glass plate. Then, immerse it in anhydrous ethanol for 10 seconds. This completes one cycle. Six cycles are required to obtain a nanofiber membrane with gold seeds.
[0070] Step 4: Add 2 ml of PVP (5%), 2 ml of ethanol, 150 μl of silver nitrate (0.1 M), and 100 μl of ascorbic acid (0.1 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 10°C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After four cycles, the PVDF / HHE@Ag nanofiber membrane (e.g., ...) is obtained. Figure 9 (As shown). The PVDF / HHE@Ag nanofiber membrane was washed with deionized water and dried at room temperature.
[0071] Example 5;
[0072] Step 1: Prepare PVDF / HHE nanofiber membrane;
[0073] N,N-dimethylformamide (DMF) and acetone were mixed in a 1:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the final mass fraction of PVDF controlled at 12% and HHE at 2% of PVDF. The mixture was magnetically stirred in water at 60°C. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0074] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0075] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 20mM chloroauric acid for 1 minute. After removal, rinse the surface with deionized water for 10 seconds, then react it in 20mM sodium borohydride for 1 minute. After removal, rinse the surface with deionized water for 10 seconds to remove any remaining solution, and squeeze out excess water using a glass plate. Then, immerse it in anhydrous ethanol for 10 seconds. This completes one cycle. Six cycles are required to obtain a nanofiber membrane with gold seeds.
[0076] Step 4: Add 2 ml of PVP (5%), 2 ml of acetonitrile, 150 μl of silver nitrate (0.1 M), and 100 μl of ascorbic acid (0.1 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 10 °C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After four cycles, the PVDF / HHE@Ag nanofiber membrane is obtained. Figure 10 The PVDF / HHE@Ag nanofiber membrane was washed with deionized water and dried at room temperature.
[0077] Example 6;
[0078] Step 1: Prepare PVDF / HHE nanofiber membrane;
[0079] N,N-dimethylformamide (DMF) and acetone were mixed in a 1:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the final mass fraction of PVDF controlled at 13% and HHE at 2% of PVDF. The mixture was magnetically stirred in water at 60°C. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0080] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0081] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 20mM chloroauric acid for 1 minute. After removal, rinse the surface with deionized water for 10 seconds, then react it in 20mM sodium borohydride for 1 minute. After removal, rinse the surface with deionized water for 10 seconds to remove any remaining solution, and squeeze out excess water using a glass plate. Then, immerse it in anhydrous ethanol for 10 seconds. This completes one cycle. Six cycles are required to obtain a nanofiber membrane with gold seeds.
[0082] Step 4: Add 2 ml of acetonitrile, 2 ml of ethanol, 150 μl of silver nitrate (0.1 M), and 100 μl of ascorbic acid (0.1 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 10 °C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After four cycles, the PVDF / HHE@Ag nanofiber membrane is obtained. Figure 11 The PVDF / HHE@Ag nanofiber membrane was washed with deionized water and dried at room temperature.
[0083] Example 7;
[0084] Step 1: Prepare PVDF / HHE nanofiber membrane;
[0085] N,N-dimethylformamide (DMF) and acetone were mixed in a 1:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the final mass fraction of PVDF controlled at 14% and HHE at 2%. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0086] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0087] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 10 mM chloroauric acid for 1 minute. After removal, rinse the surface with deionized water for 20 seconds, then react it in 10 mM sodium borohydride for 1 minute. After removal, rinse the surface with deionized water for 1 minute to remove any remaining solution, and squeeze out excess water using a glass plate. Then, immerse it in anhydrous ethanol for 10 seconds. This completes one cycle. Six cycles are required to obtain a nanofiber membrane with gold seeds.
[0088] Step 4: Add 3 ml of PVP (3%), 3 ml of acetonitrile, 3 ml of ethanol, 150 μl of silver nitrate (0.15 M), and 150 μl of ascorbic acid (0.15 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 25°C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After four cycles, the PVDF / HHE@Ag nanofiber membrane is obtained. Figure 22 ).
[0089] By fixing one end of a PVDF / HHE@Ag nanofiber membrane and rotating the other end around its own axis, a twisted PVDF / HHE@Ag nanofiber membrane can be obtained. Finally, respiratory secretions are collected using the PVDF / HHE@Ag nanofiber membrane, and SERS sensing of sweat secretions is performed using Raman spectroscopy. Figure 12 ).
[0090] By fixing one end of the PVDF / HHE@Ag nanofiber membrane and rotating the other end around its own axis, a twisted PVDF / HHE@Ag nanofiber membrane can be obtained. Finally, sweat samples were collected in situ using the PVDF / HHE@Ag nanofiber membrane and analyzed by Raman spectroscopy. Figure 20 ) and portable Raman spectrometer ( Figure 21 SERS sensing is performed on sweat secretions.
[0091] Example 8;
[0092] Step 1: Prepare PVDF / HHE nanofiber membrane;
[0093] N,N-dimethylformamide (DMF) and acetone were mixed in a 4:1 ratio as solvents. Then, a mixture of PVDF (polyvinylidene fluoride) and HHE (hydroxylamine hydrochloride) was added, with the PVDF mass fraction controlled at 10% and the HHE mass fraction at 3%. The mixture was magnetically stirred in water at 60°C. After stirring for 6 hours, a homogeneous electrospinning solution was prepared. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. All experimental procedures were conducted under ambient atmospheric conditions.
[0094] Step 2: Modify the surface of the nanofiber membrane prepared in Step 1 using anhydrous ethanol to obtain the modified nanofiber membrane;
[0095] Step 3: Remove the modified nanofiber membrane from Step 2 and immerse it in 25 mM chloroauric acid for 2 minutes. After removal, rinse the surface with deionized water for 30 seconds, then react it in 25 mM sodium borohydride for 2 minutes. After removal, rinse the surface with deionized water for 2 minutes to remove any remaining solution, and squeeze out excess water using a glass plate. Then, immerse it in anhydrous ethanol for 30 seconds. This completes one cycle. Six cycles are performed to obtain the nanofiber membrane containing gold seeds.
[0096] Step 4: Add 1 ml of PVP (8%), 1 ml of acetonitrile, 1 ml of ethanol, 50 μl of silver nitrate (0.05 M), and 50 μl of ascorbic acid (0.05 M) to 2 ml of deionized water. Place the PVDF / HHE@Au seed nanofiber membrane in the growth solution and stir magnetically at 10 °C. After 20 minutes of reaction, remove the membrane and rinse off any residual growth solution with deionized water. This constitutes one cycle. After four cycles, the PVDF / HHE@Au nanofiber membrane is obtained. Wash the PVDF / HHE@Ag nanofiber membrane with deionized water and dry it at room temperature.
[0097] This invention discloses a method for preparing surface-functionalized flexible composite fiber membranes and their applications. A PVDF / HHE@Ag nanofiber membrane is reprocessed by twisting to obtain a PVDF / HHE@Ag nanofiber membrane. After twisting, the sensitivity and signal stability of the PVDF / HHE@Ag nanofiber membrane SERS sensor are improved.
Claims
1. A method for preparing a surface-functionalized flexible composite fiber membrane, characterized in that, Specifically, the following steps are included: S1: Preparation of PVDF / HHE nanofiber membrane, specifically: mixing PVDF and HHE, using N,N-dimethylformamide and acetone as solvents to obtain mixed solution C; wherein: The mass percentage of PVDF in mixed solution C is 10-14%, the mass percentage of HHE in PVDF is 1-3%, and the mass percentage of acetone in N,N-dimethylformamide is 25-100%. A uniform electrospinning solution was prepared by magnetic stirring in water at 60℃-70℃ for 6-8 hours. PVDF / HHE nanofiber membranes were obtained by electrospinning and then dried for further use. The experimental steps were carried out under ambient atmospheric conditions. S2: The surface of the PVDF / HHE nanofiber membrane was modified using solution A to obtain the modified PVDF / HHE nanofiber membrane; S3: Immerse the modified PVDF / HHE nanofiber membrane in 10-25mM chloroauric acid for 1-2 min, rinse with deionized water, and then place it in solution B for 1-2 min. Remove the excess liquid and immerse it in anhydrous ethanol for 10-30 s. This constitutes one cycle. Obtain the PVDF / HHE@Au composite fiber membrane by repeating the above cycles two to six times. S4: PVP, acetonitrile, ethanol, silver nitrate, and ascorbic acid are added to deionized water to obtain a growth solution. The PVDF / HHE@Au composite fiber membrane is placed in the growth solution at room temperature and magnetically stirred. After the reaction, the excess liquid is removed. This constitutes one cycle. After two to six cycles, the PVDF / HHE@Ag composite fiber membrane is obtained.
2. The method for preparing a surface-functionalized flexible composite fiber membrane according to claim 1, characterized in that, In step 2, the PVDF / HHE nanofiber membrane is cut into sheets and then soaked in anhydrous ethanol for 1-2 minutes.
3. The method for preparing a surface-functionalized flexible composite fiber membrane according to claim 1, characterized in that, In step 2, solution A is anhydrous ethanol or anhydrous methanol.
4. The method for preparing a surface-functionalized flexible composite fiber membrane according to claim 1, characterized in that, In step 3, removing excess liquid specifically involves rinsing the surface with deionized water for 10-20 seconds to remove residual solution, and then squeezing out excess water using a glass plate.
5. The method for preparing a surface-functionalized flexible composite fiber membrane according to claim 1, characterized in that, In step 3, solution B is one of sodium borohydride, hydrazine hydrate, ascorbic acid, or ammonia.
6. The method for preparing a surface-functionalized flexible composite fiber membrane according to claim 1, characterized in that, The specific parameter control in step 4 is as follows: the mass fraction of PVP is 3-8%, the concentration of silver nitrate is 0.05-0.15M, and the concentration of ascorbic acid is 0.05-0.15M.
7. The method for preparing a surface-functionalized flexible composite fiber membrane according to claim 1, characterized in that, The PVDF / HHE@Ag composite fiber membrane prepared based on this method is applied to SERS sensing, specifically as follows: One end of the PVDF / HHE@Ag composite fiber membrane is fixed, and the other end is rotated around its own axis to obtain a twisted PVDF / HHE@Ag composite fiber membrane. Finally, the twisted PVDF / HHE@Ag composite fiber membrane is used for SERS sensing.
Citation Information
Patent Citations
Preparation method of flexible SERS substrate with gold-coated fiber earhead-imitated structure
CN111535022A
Synthesis of core-shell nanoparticles and applications of said nanoparticles for surface enhanced raman scattering
US20200048788A1